2019
DOI: 10.17509/jimb.v10i1.14080
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture and Intrapreneurship Employee of the Impact on Work Discipline of Employees in Brangkal Offset

Abstract: Discipline is very important for organizational growth, used primarily to motivate employees to be able to discipline themselves in carrying out work both individually and in groups. Besides that, the discipline is beneficial to educate employees to comply with and enjoy the rules, procedures, and policies that exist, so that they can produce good performance.The objectives of this study are: 1) To find out whether organizational culture and employees intrapreneurship have a partial effect on work discipline o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
2
7
0
2
Order By: Relevance
“…This research support study (Rahmah, M., & Fatmah, D., 2018;Li et al, 2006) found that the integrity of the implementation of external and internal integrity can lead to improvement of excellence compete and improve organisational performance. To build CA depends not only on internal factors but also influenced by external factors (Restrepoet al, 2016).…”
Section: Effect Of External Integration and Internal Integration To Csupporting
confidence: 76%
See 4 more Smart Citations
“…This research support study (Rahmah, M., & Fatmah, D., 2018;Li et al, 2006) found that the integrity of the implementation of external and internal integrity can lead to improvement of excellence compete and improve organisational performance. To build CA depends not only on internal factors but also influenced by external factors (Restrepoet al, 2016).…”
Section: Effect Of External Integration and Internal Integration To Csupporting
confidence: 76%
“…In addition, customer and supplier integration fully improves operational and business performance by reducing time to market, while increasing customer integration with full operational performance by shortening time to market. Gatz EI allows companies to gain knowledge about the needs of consumers (Ragatz et al, 1997). Through the integration of the value chain upstream (Ettlie and Reza, 1992).…”
Section: Effect Of External Integration and Internal Integration Of Tmentioning
confidence: 99%
See 3 more Smart Citations